Centro de aprendizaje para la primera infancia en la localidad de Bosa (2020)
In Bogotá there are around 716,781 children who are in ages between 0 and 5 years of age, making up early childhood, f r their correct development it is essential that they have scenarios where they can develop their cognitive, motor skills and achieve the acquisition of knowledge, in order to to guarantee their right to education, various educational facilities for infants have been raised, but the vast majority present a problem in common, the design of these does not take into account the characteristics of the population that will use them (way of moving, their reactions to visual, auditory, tactile stimuli and their conception of space) and also the needs of the educational model; generating a barrier in the training process, if the deficit of suitable spaces and school quotas is added to the aforementioned, the problem grows, a paradigm shift is needed in the way in which educational equipment is created and viewed to early childhood